2023
DOI: 10.3390/biology12040573
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll a Synthesis in Rhodobacter sphaeroides by Chlorophyll Synthase of Nicotiana tabacum

Abstract: The production of phytylated chlorophyll a (Chl aP) in Rhodobacter sphaeroides, which uses phytylated bacteriochlorophyll a (BChl aP), is the first step in expanding the light absorption spectra. Unlike the chlorophyll synthase (ChlG) of the Synechocystis sp. PCC6803, ChlGs of angiosperms, including Arabidopsis thaliana, Nicotiana tabacum, Avena sativa, and Oryza sativa, showed bacteriochlorophyll synthase activity and resistance to inhibition by bacteriochlorophyllide a (BChlide a), geranylgeranylated BChl a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…As widely recognized, chlorophyll plays a crucial role as a pigment in the process of photosynthesis in plants (Lin et al 2022). In previous studies, the expression level of chlorophyll synthesis‐related genes showed a positive correlation with chlorophyll content in plants (Lin and Charng, 2021, Xia et al 2021, Shah et al 2022, Kim et al 2023). We found that most of chlorophyll synthesis‐related genes were significantly down‐regulated in purple leaves, which were consistent with changes in chlorophyll content.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As widely recognized, chlorophyll plays a crucial role as a pigment in the process of photosynthesis in plants (Lin et al 2022). In previous studies, the expression level of chlorophyll synthesis‐related genes showed a positive correlation with chlorophyll content in plants (Lin and Charng, 2021, Xia et al 2021, Shah et al 2022, Kim et al 2023). We found that most of chlorophyll synthesis‐related genes were significantly down‐regulated in purple leaves, which were consistent with changes in chlorophyll content.…”
Section: Discussionmentioning
confidence: 87%
“…studies, the expression level of chlorophyll synthesis-related genes showed a positive correlation with chlorophyll content in plants (Lin and Charng, 2021, Xia et al 2021, Shah et al 2022, Kim et al 2023.…”
Section: Candidate Genes Associated With Chlorophyll Metabolism and C...mentioning
confidence: 91%
“…Chlorophyll synthase has been studied in multiple organisms such as Synechocystis ( Oster et al 1997 ), oat ( Schmid et al 2001 , 2002 ), rice ( Oryza sativa L.; Wu et al 2007 ), and tobacco ( Nicotiana tabacum L.; Shalygo et al 2009 ; Kim et al 2023 ). Two of the studies also contained comparisons to the closely related BchG of Rhodobacter capsulatus and R. sphaeroides ( Oster et al 1997 ; Kim et al 2023 ). To further advance the knowledge about the enzymatic mechanism, structural information about the proteins would be most helpful.…”
Section: Discussionmentioning
confidence: 99%